2018
DOI: 10.1186/s40409-018-0149-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic, anticancer and antigiardial activity of Palythoa caribaeorum venom

Abstract: BackgroundCnidarian venoms and extracts have shown a broad variety of biological activities including cytotoxic, antibacterial and antitumoral effects. Most of these studied extracts were obtained from sea anemones or jellyfish. The present study aimed to determine the toxic activity and assess the antitumor and antiparasitic potential of Palythoa caribaeorum venom by evaluating its in vitro toxicity on several models including human tumor cell lines and against the parasite Giardia intestinalis.MethodsThe pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
3
15
0
1
Order By: Relevance
“…Similar inhibitory effects against HepG2 cells have been reported for other jellyfish species such as Nemopilema nomurai, Cyanea lamarckii, and Acromitus flagellates venoms [35,[37][38][39][40]. Interestingly, both Acromitus flagellates venom and Cyanea lamarckii extract share three to six protein bands with R. nomadica venom in their electrophoretic patterns [35,39]. A pore-forming toxin, CcTX-1 (31.17 KDa), is an isolated proteinaceous cytotoxin from Cyanea capillata jellyfish venom that exhibited potent inhibitory activity against HepG2 cells [41,42].…”
Section: Discussionsupporting
confidence: 82%
“…Similar inhibitory effects against HepG2 cells have been reported for other jellyfish species such as Nemopilema nomurai, Cyanea lamarckii, and Acromitus flagellates venoms [35,[37][38][39][40]. Interestingly, both Acromitus flagellates venom and Cyanea lamarckii extract share three to six protein bands with R. nomadica venom in their electrophoretic patterns [35,39]. A pore-forming toxin, CcTX-1 (31.17 KDa), is an isolated proteinaceous cytotoxin from Cyanea capillata jellyfish venom that exhibited potent inhibitory activity against HepG2 cells [41,42].…”
Section: Discussionsupporting
confidence: 82%
“…Two low molecular weight toxins named PpV9.4 and PpV19.4 have been isolated from Physalia physalis venom is reported with inhibitory action of insulinsecreting activity (Diaz-Garcia et al 2012). Further, Palythoa caribaeorum's venom was investigated by Lazcano-Pérez et al was considered as an anticancer compound, as its major inhibitory effect was observed on the glioblastoma cell line and human lung cancer cells (Lazcano-Pérez et al 2018). According to another study carried out by Mirshamsi et al, Cassiopea andromeda's crude venom selectively induced ROS mediated cytotoxicity by directly targeting mitochondria, isolated from cancer tissue of patients with breast adenocarcinomas (Mirshamsi et al 2017).…”
Section: Bioactivities Of Cnidarian Toxinsmentioning
confidence: 99%
“…According to a recent study of Li et al (2012) a novel anti-oxidant protein was isolated from nematocyst extract of jellyfish Stomolophus meleagris that exhibited strong superoxide anion scavenging activity. Venom of Palythoa caribaeorum is contained peptides that show antiparasitic activity against Giardia intestinalis (Lazcano-Pérez et al 2018). Three different sea anemone toxins sticholysine I and II from Stichodactyla helianthus and equinatoxin II from Actinia equina were all found to specifically kill Giardia duodenalis and it can improve by combining with anti-Giardia antibodies (Tejuca et al 1999).…”
Section: Bioactivities Of Cnidarian Toxinsmentioning
confidence: 99%
“…The toxicity to red blood cells was determined as previously described with some modifications. 18 Briefly, erythrocytes were incubated with B. sulphurea, P. neochilus and amphotericin B at room temperature for 30 min and hemolysis was determined by the hemoglobin release, quantitated by the absorbance of the supernatants at 415nm. The percentage of lysis was calculated in relation to total lysis.…”
Section: Red Blood Cell Lysis Assaymentioning
confidence: 99%